Avaliação hidráulica de leitos de fluxo vertical plantados e não plantados em escala de demonstração - Rodolfo Carvalho Salgado Penido (2009)
Hydraulic evaluation of a system composed by three vertical flow constructed wetlands of first stage operated in parallel was accomplished for the treatment of part (100 inhabitants) of raw sewage generated in the city of Belo Horizonte, Brazil. A unit was planted with cattails (Typha latifolia), another with tiftons (Tífton-85) and the third onewas maintained without plants. Discharge hydrographs and tracer tests were undertaken for the analysis of the hydraulic behavior of the units.The obtained results indicated a strong tendency of the units to the complete mixture hydraulic regime. A great dispersion was detected in the units besides the presence of flow short circuiting and dead zones. The non saturation of the beds, even during the passage of the sheet of water was confirmed for all three units. It was highlighted the influence of the dosage regime, of the rest period and of the presence of the plants for the modeling of the hydraulic behavior of the units. The present work reinforces the aptitude of these systems for the application in small communities, once those systems are capable to comply with to rigorous performance requirements in terms of organic matter and suspended solids, even with the absence of the second stage of beds, with low per capita equivalent costs and simplicity ofoperation and maintenance.